Experiential learning with live case studies. (11th September 2020) - Neubert, Michael; Rams, Wolfgang; Utikal, Hannes
The purpose of this mixed method study is to explore the opinions of students, lecturers, and founders/CEOs about the use of live case study firms as a learning method using the theoretical framework of Kolb's experiential learning cycle. The findings suggest that the use of live case study firms in strategic management classes enhances the in-class learning experience, the quality of the group work, and the level of learning outcomes of students, produces high quality and useful output for the live case study firms, and helps a business school to develop future managers for sustainability firms. The findings of this study have a high practical significance for students, the business school, and the live case study firms. This paper also contributes to the existent literature with its constructive perspective of design learning experiences, which puts a higher emphasis on learnability through theoretical and philosophical foundations of experience-based teaching and learning.